2021
DOI: 10.3389/fimmu.2021.720025
|View full text |Cite
|
Sign up to set email alerts
|

Hallmarks of Cancers: Primary Antibody Deficiency Versus Other Inborn Errors of Immunity

Abstract: Inborn Errors of Immunity (IEI) comprise more than 450 inherited diseases, from which selected patients manifest a frequent and early incidence of malignancies, mainly lymphoma and leukemia. Primary antibody deficiency (PAD) is the most common form of IEI with the highest proportion of malignant cases. In this review, we aimed to compare the oncologic hallmarks and the molecular defects underlying PAD with other IEI entities to dissect the impact of avoiding immune destruction, genome instability, and mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 122 publications
0
14
0
1
Order By: Relevance
“…Moreover, cases with syndromic CID due to DNA repair can increase genome instability and mutation and evade growth suppression. HIES is also prone to sustaining proliferative signaling [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, cases with syndromic CID due to DNA repair can increase genome instability and mutation and evade growth suppression. HIES is also prone to sustaining proliferative signaling [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the lifetime risk of cancer developing in children with IEI has been estimated to range from 4 to 25% [ 8 , 9 ]. The most important reported mechanism of malignancy is compromised cell-mediated immunosurveillance and impaired immune function, which plays a significant role in protecting against tumors [ 10 ]. Other mechanisms are mostly associated with hematological malignancies including defects in DNA repair and impaired genetic stability, genetic predisposition, oncogenic viruses, persistent tissue inflammation and iatrogenic factors e.g., radiation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…We reported that more than one-third of IEI monogenic defects have been linked with cancer hallmarks according to the IUIS classification of 2020 [3 ▪▪ ,86]. Among 55 novel IEI genes discovered during the last 2 years [4 ▪▪ ], although the number of patients is still very limited for each disease to guarantee the association or dissociation from malignancy, we have reported here 15 genes in which cancer is a component of the main clinical phenotype observed among these rare case reports and tried to classify them mechanistically based on the known cancer hallmarks (Table 1).…”
Section: Novel Inborn Errors Of Immunity Genes Associated With Hallma...mentioning
confidence: 99%
“…On the other hand, the predominant gene deletion associated with IEI in DiGeorge syndrome (22q11.2 microdeletion) is TBX1 (T-box 1), which is also a methyltransferase (on H3K4 position similar to KMT2D), and can lead to multiorgan defects and immunodeficiency mainly because of absence of thymus and thymic development of T cells [41]. Both patients with Kabuki syndrome and Digeorge syndrome were reported to suffer from malignancies mainly lymphoma [3 ▪▪ ].…”
Section: Nonmutational Epigenetic Reprogrammingmentioning
confidence: 99%
“…Infection susceptibility may contribute to this increase. However, the mechanism of lymphomagenesis in IEI is more complex and may involve genome instability, mucosal defects permitting chronic antigen stimulation, dysregulated cellular functions, and defective tumor immunosurveillance [16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%